Motivation and Psychological Contract in the Singapore Private Banking Industry - Poh, Din Kiat (2008)
This management project seeks to understand the sources of motivation and the types of psychological contracts prevalent amongst employees in Singapore's private banking industry. Singapore's private banking industry had seen tremendous growth in the last few years with the Government's push to make it the Switzerland of Asia. This growth has resulted in high demand for talent and high turnover rates. It is often said that money is not the key reason why people stayed motivated. Part of this project seeks to study an employee's source of motivation in his current job, managers' perceptions on employee motivation, and the key factors contributing to an employee's intention to leave an organisation. In the second part of the project, I would like to uncover the prevalent type of psychological contracts amongst employees in Singapore's private banking industry, the type of psychological contract obligations employees value most (Lester & Kickul, 2001), and their experiences on psychological contract. Through this project, I hope to provide an insight into staff motivation and psychological contract in the private banking industry as these factors influence organisational change management, employee satisfaction, productivity, and retention.